KEPENTINGAN INDONESIA MELAKUKAN IMPOR BUAH JERUK DARI TIONGKOK - Karina Saphira; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This paper is a bilateral trade study that provides an analysis of the Cooperation of two countries in the fulfillment of needs and achieve their national interests. The researcher focused on Indonesia's Importance of Importing orange fruits from China. For Indonesia's local orange production is less, the production of crude in Indonesia in 2014 is only 1.93 million tons. While Indonesia imports from China as much as 3.5 million tons in 2015, so not much national production of orange Indonesia and not yet meet the national needs. And this is the main reason why Indonesia keeps importing orange fruits from China.This paper uses theory of International Trade, in this case the theory of trade/ comparative because there is competition in this orange fruit in the Indonesian market originating from China with local oranges, so it takes a significant Indonesian government policy in the process of buying and selling Chinese orange fruit and fruits Local oranges. Supported by National Nation's analysis level and Liberalism Perspective. The concept leads to qualitative methods and field studies and is assisted by literature studies as a source of information.Indonesia's bilateral relationship with China is definitely China's largest trading partner in Indonesia. Seen from the trade value of 47 billion dollars in 2016. The number of exports is smaller than the amount of imports indicates that for citrus commodities, the state of Indonesia for its domestic consumption is still dependent on imports from other countries. Also influenced by the price policy, taste, and marketing orangesKeywords: Interests, Import, Orange, Tiongkok and Trade